A long life in good health: subjective expectations regarding length and future health-related quality of life - Rappange, David R. (Eur J Health Econ, 2015)
BACKGROUND: Subjective life expectancy is considered relevant in predicting mortality and future demand for health services as well as for explaining peoples’ decisions in several life domains, such as the perceived impact of health behaviour changes on future health outcomes. Such expectations and in particular subjective expectations regarding future health-related quality of life remain understudied. The purpose of this study was to investigate individuals’ subjective quality adjusted life years (QALYs) expectation from age 65 onwards in a representative sample of the Dutch generic public. METHODS: A web-based questionnaire was administered to a sample of the adult population from the Netherlands. Information on subjective expectations regarding length and future health-related quality of life were combined into one single measure of subjective expected QALYs from age 65 onwards. This subjective QALY expectation was related to background, health and lifestyle variables. The implications of using different methods to construct our main outcome measure were addressed. RESULTS: Mean subjective expected QALYs from age 65 onwards was 11 QALYs (range −9 to 40 QALYs). Individuals with unhealthier lifestyles, chronic diseases, severe disorders or lower age of death of next of kin reported lower QALY expectations. Indicators were varyingly associated with either subjective life expectancy or future health-related quality of life, or both. CONCLUSION: Extending the concept of subjective life expectancy by correcting for expected quality of life appears to generate important additional information contributing to our understanding of people’s perceptions regarding ageing and lifestyle choices.